The Unreliability of Ageing Narrative in John Banville’s The Sea and Ancient Light - Li, Huifang; Li, Junlin (Advances in Social Sciences Research Journal, 2023)
The Sea and Ancient Light were both written after the author John Banville has reached his sixties. As a writer with a strong consciousness of age identity, Banville interwove his age concern with his narrative techniques in these two works. Among them, the unreliability of the protagonists’ narrative is the most distinct feature and it was carried out through three aspects. First, Banville deliberately inserts self-blurring narratives to indicate the symptom of amnesia which is popular among the aged group; Second, the recurrent self-referential fabricated details imply a confusion between reality and fancy in the aged life and the difficulty in maintaining the aged self; Third, invention and imagination is encouraged as a way to restore the self-identification of the elders. Therefore, the commonly labelled postmodern narrative of Banville is rather a realistic depiction of the aged life.